The Influence of Transformational Leadership on Teacher Commitment towards Organization, Teaching Profession, and Student Learning in Secondary Schools in Miri, Sarawak, Malaysia - Mee Ling, Sii Ling @ (EDUCARE, 2012)
ABSTRACT: A principalâs role is critical in sustaining or diminishing teacher commitment. Teacher commitment recorded only average in Malaysia. Accordingly, the researcher is interested in studying the relationship between transformational leadership and teacher commitment in the educational institution, exclusively in the government secondary schools in Miri, Sarawak, Malaysia. The survey instrument was developed based on conceptual framework on transformational leadership, teacher commitment, and literature review. Quantitative survey method was applied and four broadly hypothesized relationships were tested with a sample of 1,014 trained teachers serving in twenty-seven secondary schools in Miri, Sarawak. The findings showed either direct or indirect relationship between transformational leadership, teacher commitment, and moderators. They offer insights on how leadership practices affect teachersâ commitment and sense of teaching efficacy. It also necessitates for leadership development of school leaders to acquire transformational leadership qualities that are crucial in changing teachersâ attitude and improving their commitment level. Future endeavors should compare these findings with similar predictors, criterion, and moderators in other areas.KEY WORDS: School leadership, principalâs role, teacher commitment, transformational leadership, and educational institution in Sarawak, Malaysia.Â Â About the Author: Sii Ling @ Mee Ling is a Ph.D. Student at the Faculty of Education UM (University of Malaya), Kuala Lumpur, Malaysia. For academic purposes, she can be contacted at: Lot 822, Bunga Raya 4, Taman Bumiko, 98000 Miri, Sarawak, Malaysia. E-mail: me2867sl@yahoo.comHow to cite this article? Mee Ling, Sii Ling @. (2012). âThe Influence of Transformational Leadership on Teacher Commitment towards Organization, Teaching Profession, and Student Learning in Secondary Schools in Miri, Sarawak, Malaysiaâ in EDUCARE: International Journal for Educational Studies, Vol.4(2) February, pp.155-178. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 9, 2011); Revised (January 10, 2012); and Published (February 17, 2012).